The Role of Logistics Service Providers in the Distribution Channel of Imported Perishable and Processed Food Product to Java Island, Indonesia - Megita Ryanjani Tanuputri; Ravipim Chaveesuk; Adi Djoko Guritno (APTA and DTIP FTP UGM, 2017)
Today fierce competition has highly enforced the company to focus more on their core competency and has encouraged them to strengthen competitive advantage. This condition reinforces the role of logistics service providers (LSP) to help company run their supporting activities. This research aims to identify the characteristics of LSP and to analyze their role in the distribution channel of imported perishable and processed food products in Indonesia. Convenience sampling was employed as sampling methodology and in-depth interview was used to collect detail information from respondents including private stakeholders, port authorities, freight forwarder association and retailers. The research results show that the characteristics and size of the company affects the involvement of LSP in the distribution channel. The roles of freight forwarders (FF) extensively include pre-customs clearance, customs clearance and post-customs clearance. Furthermore, the role of FF considerably contributes to the ease of arranging international shipment. The role of distributor plays vital role in the tracking and tracing system and timeliness of distribution channel. Meanwhile, the role of FF and transporter is fairly low in encouraging track-able and traceable distribution channel. Further improvements are needed to encourage better distribution channel performance.